American education in the age of mass migrations 1870 - 1930 - Fabrice Murtin; Martina Viarengo (Institute for the Study of Labor (IZA), 2009)
This paper derives original series of average years of schooling in the United States 1870-1930, which take into account the impact of mass migrations on the US educational level. We reconstruct the foreign-born US population by age and by country of origin, while combining data on the flow of migrants by country and the age pyramids of migrants by country. Then we use original data on educational attainment in the nineteenth century presented in Morrisson and Murtin (2008) in order to estimate the educational level of US immigrants by age and by country. As a result, our series are consistent with the first national estimates of average schooling in 1940. We show that mass migrations have had a significant but modest impact on the US average educational attainment. However, the educational gap between US natives and immigrants was large and increased with the second immigration wave, a phenomenon that most likely fostered the implementation of restrictive immigration rules in the 1920s.
urn:nbn:de:101:1-2009021035
Keywords: I2; J24; N70; O1; 330; Education; migrations; economic history; economic development research; Bildung; Einwanderung; Bildungsniveau; Migranten; Soziale Integration; USA